2020
DOI: 10.1037/pst0000337
|View full text |Cite
|
Sign up to set email alerts
|

Using termination as an intervention (UTAI): A view from an integrative, cognitive-existential psychodynamics perspective.

Abstract: Treatment termination is, arguably, one of the most important events in the course of psychotherapy. In the present article, we present an approach to termination that views the latter as a key intervention. Developed from an integrated, cognitive-existential psychodynamics (CEP) perspective (Shahar & Govrin, 2017), Using Termination as an Intervention (UTAI) is a prescheduled, albeit tentative, treatment termination that may be used as an intervention for patients' remoralization (Howard, Kopta, Krause, & Orl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Two special issues dedicated to termination in the journal Psychotherapy (2017 and 2020) included papers devoted to different perspectives on termination. These papers explored termination in short-term, psychodynamic treatment (16 sessions; Harrison, 2020), cognitive behavioral dynamic therapy (Shahar & Ziv-Beiman, 2020), and cognitive behavior therapy (Vidair et al, 2017). Norcross et al (2017) studied the commonalities in termination across these theoretical orientations and found that there were some things that all therapists did when helping their clients end therapy.…”
Section: Mutual Terminations: Agreed-on Endingsmentioning
confidence: 99%
“…Two special issues dedicated to termination in the journal Psychotherapy (2017 and 2020) included papers devoted to different perspectives on termination. These papers explored termination in short-term, psychodynamic treatment (16 sessions; Harrison, 2020), cognitive behavioral dynamic therapy (Shahar & Ziv-Beiman, 2020), and cognitive behavior therapy (Vidair et al, 2017). Norcross et al (2017) studied the commonalities in termination across these theoretical orientations and found that there were some things that all therapists did when helping their clients end therapy.…”
Section: Mutual Terminations: Agreed-on Endingsmentioning
confidence: 99%